Comparative Study of Heavy Metal Accumulation in Kidney of Gallus gallus Within Polluted Areas in Wasit Province - Ali, Amjaad; Alattabi, Ryam; Kadhim, Sajjad; Aleiqabie, Rafel; Al-Hamadiny, Shahad (Journal of Biomedicine and Biochemistry, 2023)
Introduction Continued extraction of oil and the manufacturing of brick from brick factories in Wasit province has made the amount of heavy metals discharged into the atmosphere is gradually grow. As a result, ex- cessive amounts of these pollutants can accumulate and intoxicate humans and animals living nearby, posing a threat to ecosystems, wildlife, and human health.Methodology In this study, concentrations of Lead (Pb), cadmium (Cd), zinc (Zn), iron (Fe), and copper (Cu), were measured in kidney tissue of Gallus gallus being collected from two polluted sites near Al-Ahdeb oil field and Al-Hay brick factories in Wasit province.Results and Discussion Accumulation levels indicated in this study were significantly higher in samples taken from Al-Hay brick factories than those taken from Al-Ahdeb oil fields, except for Lead (Pb), which was detected to be higher in samples of Al-Ahdeb oil fields. All concentration levels detected were high and considered hazardous to the health of organ- isms habituating within polluted areas since accumulation in tissues was reported to cause harmful negative effects on kidney function.Conclusion Accumulation levels indicated in this study were signifi- cantly higher in samples taken from Al-Hay brick factories than those taken from Al-Ahdeb oil fields. All concentration levels detected were high and considered hazardous to the health of organisms habituating within polluted areas.